Development of an artificial 3D liver phantom for analysis of radiotherapeutic effects in vitro - Stengl, Christina; Ghafoory, Shahrouz; Weidner, Artur; Murphy, Brennah; Wölfl, Stefan (Applied Sciences, 2022)
Over recent decades, stereotactic body radiotherapy has garnered increasing popularity. Unfortunately, conventional preclinical 2D in vitro models are often insufficient for studying radiotherapy effects. Therefore, in this study, we developed a novel anthropomorphic in vitro liver phantom, which simulates the relevant hepatocellular carcinoma (HCC) tumor microenvironment and spatial organization. The liver phantom was 3D printed, filled with tissue-mimicking agarose mixture, and designed to fit ten microfluidic chips (MCs), in which HepG2 cells were seeded. Airtight MCs induced hypoxic conditions, as verified by Hif1α staining. Irradiation was conducted with 20 Gy in one fraction using a CyberKnife, in either a 2D setup, or by irradiating MCs arranged in the 3D-printed liver model using an individually calculated treatment plan. Post-irradiation cellular damage was determined via γH2AX staining. Here, we demonstrate a new physiologically relevant approach to model HCC pathology following radiotherapy. Comparing γH2AX staining in normoxic conditions to cells grown in MCs (hypoxic conditions) revealed a reduction in cellular damage of 30.24% (p = 0.0001) in the hypoxic environment. Moreover, we compared the scattering effect of radiation on a conventional 2D in vitro model to our new 3D anthropomorphic liver phantom and observed a significant γH2AX intensity reduction of 9.6% (p = 0.0294) in HepG2 cells irradiated in the phantom. Our approach of utilizing a liver phantom takes into account the hypoxic tumor microenvironment and 3D scattering effects of tissue irradiation, thereby modeling both physical and biological parameters of HCC tumors. The use of tissue phantoms lays the groundwork for future examination of other hypoxic tumors and offers a more comprehensive approach for screening and analysis of novel cancer therapeutics.
Gesehen am 11.01.2023